PERANCANGAN PENILAIAN KINERJA PEGAWAI BERDASARKAN KOMPETENSI SPENCER - Hidayat, Dayat (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
Human resource is one among most important resources within organizations. Leaders of organizations should be able to recognize and utilize their human resource comptences in order to develop the organizations. A performance assessment instrument is needed to measure the personels? competence. Within governmental institutions, the conventional way of measuring the civil servants? competence is through DP3. Now, there are some other alternatives in doing so. One of the instruments is based on Spencer Competency Model.